The Effectiveness of Using Telegram Group for Vocabulary Acquisition for Junior High School Students - Ulfiah Azzahra; Eusabinus Bunau; Luwandi Suhartono; Eka Fajar Rahmani; Yohanes Gatot Sutapa Yuliana (Nusantara Journal of Multidisciplinary Science, 2024)
This research investigated how Telegram Group improved students' vocabulary achievement in terms of word class, consisting of nouns, verbs, adjectives, adverbs, word meanings, and language usage among the grade eight students at SMP Negeri 25 Pontianak. A pre-experimental design was used in the investigation. Enrolment in the study was limited to ninety-four children from eight grade levels (A, B, and C). A total of 32 students from 8B were used as a sample in this study. The research data was derived from the outcomes of both the pre- and post-tests. With a total of thirty items, the test was comprised of multiple-choice questions. Microsoft Excel was used for the data analysis. There was a marked improvement between the results of the pre- and post-tests. Data analysis revealed that after the test, the average score was 89.84, up from 68.53 before the test. Moreover, the effect size was 1.728, suggesting that the alternative hypothesis “The use of Telegram group is effective on vocabulary acquisition of eighth-grade students of SMP Negeri 25 Pontianak” was accepted. Based on the acceptance of the hypothesis, it is suggested that teachers use Telegram Group more often in teaching vocabulary.